PedLER: Pediatric Longitudinal Experience with Residents - Weidman, Danielle; Scott, Ori; Jewitt, Natalie; Jamal, Alisha; Harel-Sterling, Maya; Au, Hosanna; Punnett, Angela (Canadian Medical Education Journal, 2019)
Pediatric Longitudinal Experience with Residents (PedLER) is a unique program at the University of Toronto, designed to foster formal mentorship between pediatric residents and first-year medical students.